Historical aspects of public administration in education of Ukraine - Shorobura, Inna Mykhailivna (Journal of Education, Health and Sport, 2021)
The article covers the historical aspects of public administration in education ofUkraine. The process of transition to another form of education administration was difficult and extended, as there was no experience, conditions and challenging socio-political situation in the country complicated the process. The powers of public self-government bodies are defined by special laws and constituent documents. The combination of state and public administration in education creates public administration that proclaims the priority of the state with the obligatory consideration of public opinion.